Hydrogen sulfide: role in ion channel and transporter modulation in the eye - Njie-Mbye, Ya Fatou; Opere, Catherine A.; Chitnis, Madhura; Ohia, Sunny E. (Frontiers in Physiology, 2012)
Hydrogen sulfide (H2S), a colorless gas with a characteristic smell of rotten eggs, has been portrayed for decades as a toxic environmental pollutant. Since evidence of its basal production in mammalian tissues a decade ago, H2S has attracted substantial interest as a potential inorganic gaseous mediator with biological importance in cellular functions. Current research suggests that, next to its counterparts nitric oxide and carbon monoxide, H2S is an important multifunctional signaling molecule with pivotal regulatory roles in various physiological and pathophysiological processes as diverse as learning and memory, modulation of synaptic activities, cell survival, inflammation and maintenance of vascular tone in the central nervous and cardiovascular systems. In contrast, there are few reports of a regulatory role of H2S in the eye. Accumulating reports on the pharmacological role of H2S in ocular tissues indicate the existence of a functional trans-sulfuration pathway and a potential physiological role for H2S as a gaseous neuromodulator in the eye. Thus, understanding the role of H2S in vision-related processes is imperative to our expanding knowledge of this molecule as a gaseous mediator in ocular tissues. This review aims to provide a comprehensive and current understanding of the potential role of H2S as a signaling molecule in the eye. This objective is achieved by discussing the involvement of H2S in the regulation of (1) ion channels such as calcium (L-type, T-type and intracellular stores), potassium (KATP and small conductance channels) and chloride channels, (2) glutamate transporters such as EAAT1/GLAST and the L-cystine/glutamate antiporter. The role of H2S as an important mediator in cellular functions and physiological processes that are triggered by its interaction with ion channels/transporters in the eye will also be discussed.